Molecular Characterization of Hemoparasites and Hemoplasmas Infecting Domestic Cats of Southern India - Malangmei, Lanchalung; Ajith Kumar, Karapparambu Gopalan; Nandini, Ashwathappa; Bora, Christophe Angeline Felicia; Varghese, Anju; Amrutha, Birur Mallappa; Kurbet, Prashant Somalingappa; Pradeep, Rangapura Kariyappa; Nimisha, Murikoli; Deepa, Chundiyil Kalarickal; John, Lijo; Ravindran, Reghu (Frontiers in Veterinary Science, 2021)
In the present study, 111 blood samples were collected from apparently healthy cats belonging to four districts of Kerala, southern India, and they were investigated for the presence of hemoparasites and hemoplasmas by light microscopic examination and polymerase chain reaction (PCR). The microscopic examination of the Giemsa-stained blood smears did not reveal any parasites/organisms. However, PCR followed by nucleotide sequencing could detect 10 (9.01%) out of 111 samples infected with Hepatozoon felis, 3 (2.70%) with Cytauxzoon spp., and 10 (9.01%) with Mycoplasma spp. None of the samples revealed amplicons specific for the Babesia spp. and Trypanosoma evansi. The phylogenetic analysis of 18S ribosomal RNA (rRNA) gene sequences of H. felis revealed the existence of two different populations of H. felis circulating in the blood of infected cats. The phylogenetic tree was constructed based on 18S rRNA gene sequences of Cytauxzoon spp. and revealed that these isolates formed a distinct clade and do not cluster with any of the isolates from other countries. Among the 10 samples positive for Mycoplasma spp. infections, 7 were detected positive for Candidatus Mycoplasma haemominutum, two for Mycoplasma haemofelis, and one for Candidatus Mycoplasma turicensis. Phylogenetic analysis of 16S rRNA gene sequences of Mycoplasma spp. showed no distinct geographical grouping of the sequences. The sequences of M. haemofelis, Candidatus M. haemominutum, and Candidatus M. turicensis identified in the study clustered along with their respective isolates from around the world. To the best of our knowledge, this study forms the first report of molecular detection of Cytauxzoon spp. and Candidatus M. turicensis in cats from India.